Global scattered-light spectrography for laser absorption and laser–plasma instability studies - Yihang Zhang; Zhe Zhang; Xu Zhao; Kevin Glize; Yufeng Dong; Xiaohui Yuan; Yutong Li; Jie Zhang (High Power Laser Science and Engineering)
An optical spectrometer system based on 60 channels of fibers has been designed and employed to diagnose light emissions from laser–plasma interactions. The 60 fiber collectors cover an integrated solid angle of